The Benefits of Being a ?Buddy?: Exploring the Medical Student Experience As Mentor to Minority High-School Students (Mary Ann Liebert, 2021)
Purpose: The Aspiring Doctors Precollege Program at Ohio University Heritage College of Osteopathic Medicine serves to introduce underrepresented minority (URM) high-school students to careers in health care as well as introducing URM high-school students to medical student mentors. Each month, medical students and their student mentees connect through a variety of activities on the medical college campus. While the program has significant benefit for the mentees, it also provides professional development opportunities for the medical students as mentors. Many researchers have written on the value of mentored relationships between medical students and established physicians; however, exploring the benefits of medical student mentorship has yet to be discussed in the literature. Objectives: The primary objectives of this study are to understand medical student perceptions of being a mentor and describe the contributions to their medical education. Methods: Semistructured interviews were conducted with student mentors regarding their experiences serving in this program. These interviews were inductively coded for significant ideas, themes, and patterns. Results: A series of 12 research interviews were conducted with medical students who have participated in The Aspiring Doctors program for at least three semesters. Major themes that emerged from the analysis include the following: the importance of guidance in medicine through person-to-person mentoring, and identification of future career aspirations. Summary/Conclusions: Medical student mentors found this program to be a valuable addition to their educational experience. Mentoring URM high-school students offers pre-clinical medical students the opportunity to connect with their community and envision themselves serving as physicians in underresourced communities. Simultaneously, it provides a meaningful way of paying-it-forward during their education. Further studies can be done to track the outcomes of the medical students with respect to their designations stated while participating in this program, the role of mentorship on professional identity development, and possible effects on preventing/mitigating burnout.